Conceived in Liberty: Acknowledging the Human Rights of the Unborn Through Opposing Gendercide - Gamble, Nathan; Gamble, Joel (The Meducator, 2014)
Sex-selective abortion, also colloquially referred to as “gendercide”, has become an increasingly prevalent issue. Technological advancements have allowed parents to know the sex of their child in utero. In some ethnic groups, parents frequently abort their unborn child (almost always female) if the sex does not align with cultural desires and pressure. 1 In India and China, the problem has become so endemic that physicians are barred from notifying parents of the sex of their baby in utero. This, however, has done little to curb the problem. 2